Mechanical properties of intermetallic compounds in electrodeposited multilayered thin film at small scale by nanoindentation - Rahman, A.M.S.; Chia, P.Y.; Haseeb, A.S. Md. Abdul (Materials Letters, 2015)
Mechanical properties of intermetallic compounds (IMCs) which were formed in electrodeposited Cu/Sn and Cu/Ni/Sn multilayered thin film have been investigated. The layers of Cu, Sn and Ni were formed by electrodeposition technique using copper pyrophosphate, tin methanesulfonic and nickel Watts baths, respectively. After synthesis, samples were subjected to high temperature aging at 150 degrees C for 168 h. Two different types of intermetallics Cu3Sn and Cu6Sn5 were formed in Cu/Sn. After adding ultra-thin layer of Ni (70 nm) in between Cu and Sn layers, (Cu, Ni)(6)Sn-5 was formed after aging at similar condition to that of Cu/Sn. Tin whisker growth was not observed in both samples after preserving the samples in air for 365 days. Hardness and elastic moduli of all three different types of IMCs were measured by using a Hysitron Triboindenter 750 Ubi system. Hardness of the three IMCs Cu3Sn, Cu6Sn5, (Cu, Ni)(6)Sn-5 and Cu were found to be 5.99, 6.61, 7.43 and 1.55 GPa, respectively. The addition of Ni suppressed the growth of Cu3Sn greatly. This is expected to lead to better reliability of electronic interconnections as Cu3Sn is often associated with void formation. (C) 2015 Elsevier B.V. All rights reserved.